Family history of diabetes and glycemic progression: A propensity score-based analysis using health checkup data - Sangtaek Oh; Seongtae Kim; Jaesuk Yun; Jung Kee Min; Hee-Jung Jee; Tae-Young Heo (PLoS ONE, 2026)
Background Family history of diabetes mellitus (FH_ DM) is a well-established risk factor for diabetes, but most studies have focused on disease incidence rather than glycemic changes over time. Understanding how FH_ DM affects the magnitude of change in blood glucose biomarkers before clinical diagnosis can inform earlier intervention strategies and optimize screening intervals. Methods We analyzed standardized health checkup data from Korean adults aged 20 years or older with repeated measurements over approximately 2-year (n = 25,647) and 4-year (n = 12,831) intervals. Using propensity score matching (PSM), inverse probability of treatment weighting (IPTW), and doubly robust (DR) estimation, we estimated the average treatment effect of FH_ DM on changes in fasting blood glucose (FBG) and hemoglobin A1c (HbA1c). The analytic cohort included individuals with normoglycemia, prediabetes, and diabetes. Sensitivity analyses using robustness values assessed potential unmeasured confounding. Findings After adjusting for 49 measured confounders, individuals with FH_ DM showed consistently greater glycemic progression than those without FH_ DM across all methods. Over 2 years, HbA1c showed a 0.02% greater increase (95% CI: 0.01–0.03) and FBG showed a 0.3 mg/dL greater increase (95% CI: 0.1–0.6) in the FH_ DM group. Over 4 years, the difference in FBG change was 1.3–1.9 mg/dL. Results remained robust when excluding individuals on diabetes medication and across sensitivity analyses. Conclusions Family history of diabetes is independently associated with greater glycemic progression across the normoglycemia-to-diabetes spectrum, even after rigorous adjustment for confounding. These findings support the use of FH_ DM as a practical marker for risk-stratified screening strategies. Individuals with FH_ DM may benefit from more frequent glucose monitoring and earlier preventive interventions to delay or prevent diabetes onset.